Technology Advancement and Customer Satisfaction in Restaurant Industry in the UK - Ajdini, Lorela; Datta, Palto (Archives of Business Research, 2025)
Purpose: This study aims to find the key determinants of customer satisfaction and to examine the relationship between technology and customer satisfaction. This study gives a critical analysis of how technology affects restaurant customer loyalty.Methodology: Positivism philosophy, deductive approach and quantitative research methods are used to conduct the research. Furthermore, a survey is used as a strategy combined by a stratified sampling strategy, to collect primary data from a sample of 100 restaurant customers ensuring validity and reliability of the study through statistical analysis. Results of the study: The results of the study found a positive correlation between technological adoption and customer loyalty, and the changing effects of technology on operational efficiency and service quality with important contributions coming from factors like perceived ease of use and positive effects on restaurant environment. Practical Implications and conclusions: Based on the findings it is imperative that restaurant owners need to adjust their technology adoption strategies to consider various demographic groups. Businesses can increase client satisfaction and loyalty by using creative solutions that boost operational efficiency and service quality. It also contributes to academic literature and sheds light on customer satisfaction in the restaurant industry. Originality/Value: This study demonstrates the value of user-friendly technology and the perceived improvement in restaurant atmosphere by confirming a positive relationship between technology use and customer satisfaction. It provides insightful information on the diverse preferences of various demographic groups, enlightening restaurant businesses about the significance of customised technology integration strategies.